The Re-alignment of Post-Secondary Education Systems in Canada - Gregor, Alexander (Canadian Journal of Higher Education, 1979)
This paper is concerned with the attempts that have been made in Canada during the 1960's and 1970's to define and develop systems of post-secondary education to include the various forms of institutions at that level (i.e., the universities, community colleges, technical institutes, etc.). Particular emphasis is placed on the attempts to define the appropriate relationships between the universities and the relatively new community college sector. Attention is given to the quite different nature of that latter sector in the various provincial jurisdictions, and to the more general issues that must be addressed in any attempt to co-ordinate institutions based on quite different goals and natures. The paper concludes that there are very clear limits that must be observed in any efforts to produce efficient and coordinated systems of higher education, if violence is not to be done to the basic nature and purposes of the constituent institutions.